Peningkatkan Minat Dan Hasil Belajar Siswa Menggunakan Pembelajaran Kelompok Dengan Teknik Permainan Karet Pada Pengurangan Bilangan Sampai 100 Di Kelas II SDN Sogaan II – Probolinggo - Syaiful Haq; Ludfi Arya Wardana; Didit Yulian Kasdriyanto (CV. ITTC INDONESIA, 2023)
Efforts to improve the quality of education must be holistic, including knowledge, skills, attitudes and values. Here, educators become the main factor in improving the quality of education. Educators must be competent in the use of learning strategies and methods. The motivation for this study is the problems that arise in the learning of 2nd grade mathematics of SDN SOGAAN II - PROBOLINGGO, students are unable to understand the concepts of subtraction of even numbers and subtraction of numbers one and the use learning materials in teaching and the learning process is not very interesting, lack of interests and learning outcomes for category 2 SDN SOGAAN II - PROBOLINGGO. So we need a treatment to solve this problem. For this reason, researchers use rubber games for group learning to increase interest and learning outcomes. The study was conducted using the Classroom Action Research (CAR) method and the data analysis used a circular qualitative approach to measure learning outcomes. The application of group learning and rubber games has a positive impact on improving student learning outcomes, and student learning outcomes have increased in the second cycle. In Cycle I, students achieved an overall average learning outcome of only 73.75, which was considered insufficient to meet academic performance goals, while in Cycle II, they achieved 82.4. This means that group learning through rubber games is very effective in increasing student interest and learning outcomes.